DESKRIPSI TENTANG KEHIDUPAN MASYARAKAT PETANI DI DESA PULUNG KENCANA KECAMATAN TULANG BAWANG TENGAH KABUPATEN TULANG BAWANG BARAT - Nunik Syamsyiah; Ali Imron; Wakidi Wakidi (FKIP UNIVERSITAS LAMPUNG, 2013)
Most of the society in Pulung Kencana Village are peasants. Their life has been changed in line of the time. The purpose of this research is to describe social change on the peasants society in the Village of Pulung Kencana sub district of Tulang Bawang Tengah Regency of Tulang Bawang Barat. The method used in this research is descriptive method and used interviews, observations, literature and documentation as the technique of collecting data. Data analysis technique is a qualitative data analysis techniques. The result of the research sows that there has been a change in the agricultural land management (Gogo rice became kind of rice that planed in the field whereas some of them changes to latex), mutual cooperation work system being employed voluntarily to workers, tolerance and intimate among members of the public more reduced as well as the change from the peasants groups to the Joint peasants Groups (Gapoktan) which was formed on March 10, 2007. It can be conclude that the social change which includes changes in social behavior, social interaction and social institutions. The Social change happens slowly or evolution that changes as society adapts to environmental conditions. Keywords: social change, society, peasants